Learn, adapt, and move on: An interview with Rajesh Lingappa - LINGAPPA, Rajesh (Institutional Knowledge at Singapore Management University, 2020)
Rajesh Lingappa, co-founder and former chief technology officer of RedMart, talks about his entrepreneurial journey in the world of technology.